Breakfast consumption among students in UiTM Cawangan Kelantan / Anis Athirah Abdul Rahim…[et al.] - Abdul Rahim, Anis Athirah; Efandi, Nurfarazila; Ruslan, Nurul Athirah Syuhadah; Mohd Azhar, Nur Maisarah (2019)
Nowadays, mostly people and especially among students assume that breakfast is not too important for them and this phenomena has been regarded as normal. However, study of Malaysian Malnutrition showed that one over ten Malaysian person did not consume breakfast. Some of the reasons for not taking breakfast are not hungry, not have enough times and has no appetite. Some research show that relation between consuming breakfast and weight management. One of the research by obesity research journal by 2002 reported 3000 volunteer in USA found that 78 percent from them managed to lose weight and maintain weight by daily intake of breakfast. The result found out that consuming breakfast every day is common form for maintaining lose weight. Experienced consultant, Siew Wei Tee stated, those who leave breakfast are seen tend to choose food that contain high calorie for the next meals. For a long time, it can lead to the formation of chronic disease.